Colitis-Induced Pancreatic Fistula with Pancreatic Ascites - Evan Winrich; Ethan Steele; Amal Shine; Dipendra Parajuli (Case Reports in Gastroenterology)
Introduction: Although cases of severe pancreatitis causing fistula formation into the colon have been documented, the reverse process of colitis causing a pancreatic fistula remains undocumented. Case Presentation: We present the case of a 79-year-old male with severe colitis resulting in perforation and pericolonic abscess formation adjacent to the pancreas, which resulted in an internal pancreatic fistula and pancreatic ascites. After 2 paracenteses, our patient ultimately underwent endoscopic retrograde cholangiopancreatography (ERCP) with sphincterotomy and pancreatic duct stent placement. The patient clinically improved and was ultimately discharged. Conclusion: Follow-up ERCP was performed 2 months after discharge and showed no contrast extravasation, illustrating closure of the previous pancreatic fistula. Ultimately, our case demonstrates that cases of severe colitis may contribute to adjacent pancreatic fistula and ascites formation.